PSYCHOLOGICAL CONTENT IN ISLAMIC EDUCATION TEXTBOOK: A REQUIREMENT IN CHARACTER BUILDING GOALS ACHIEVEMENT - Lenny Herlina (Jurnal Tatsqif, 2020)
The study aims to find out whether psychological content is presented in Islamic education textbooks or not. The method used was library research. The data collection technique used was by reviewing the document and descriptive analysis. The textbooks studied were: first, Islamic Religious Education and Character student textbook of Class 10 by Kemendikbud RI in 2017, second, the book entitled “Spirituality, Values and Mental Health: Jewels for the Journey” edited by Mary Ellen Coyte, Peter Gilbert, and Vicky Nicholls. The research result shows that there is not psychological content within the books. While according to the researcher, psychological content is very important to enrich Islamic Education learning material as a means to instil religious awareness related to spiritual values, such as good personality both personally and socially as the initial and final objective in the Islamic Religious Education learning process. The research result is expected to influence Muslims with individual and social piety by eliminating the self-righteousness attitude that often creates inter-faith and internal Muslim bullying as well as eradicating the assumption that Muslims are intolerant and not humanist as part of the indications of the achieved character building.